2005
DOI: 10.1128/mcb.25.15.6355-6362.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional but Abnormal Adult Erythropoiesis in the Absence of the Stem Cell Leukemia Gene

Abstract: Previous studies have indicated that the stem cell leukemia gene (SCL) is essential for both embryonic and adult erythropoiesis. We have examined erythropoiesis in conditional SCL knockout mice for at least 6 months after loss of SCL function and report that SCL was important but not essential for the generation of mature red blood cells. Although SCL-deleted mice were mildly anemic with increased splenic erythropoiesis, they responded appropriately to endogenous erythropoietin and hemolytic stress, a measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
2
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 41 publications
4
45
2
2
Order By: Relevance
“…These data showed that HSC development and function is not dependent on SCL expression once specification of the hematopoietic fate in the early embryo has been achieved. Yet, SCL remains essential for maintaining proper differentiation of primitive and definitive erythroid and megakaryocyte lineage cells in the yolk sac, fetal liver, and bone marrow (15,17,18). These findings contradict existing paradigms of lineage specification, in which continuous expression of the transcription factor that specifies a lineage is required to maintain the lineage, and suggests that SCLinduced hematopoietic specification is a stable cell fate that is not challenged with loss of SCL later on in development.…”
Section: Commitment To the Hematopoietic Fatecontrasting
confidence: 54%
“…These data showed that HSC development and function is not dependent on SCL expression once specification of the hematopoietic fate in the early embryo has been achieved. Yet, SCL remains essential for maintaining proper differentiation of primitive and definitive erythroid and megakaryocyte lineage cells in the yolk sac, fetal liver, and bone marrow (15,17,18). These findings contradict existing paradigms of lineage specification, in which continuous expression of the transcription factor that specifies a lineage is required to maintain the lineage, and suggests that SCLinduced hematopoietic specification is a stable cell fate that is not challenged with loss of SCL later on in development.…”
Section: Commitment To the Hematopoietic Fatecontrasting
confidence: 54%
“…A drop in cellular Ter119 expression was observed in addition to suppressed erythroid development in the bone marrow of LSD1-kd mice (Figure 4g). Interestingly, lower Ter119 expression is a feature of SCL-deficient erythropoiesis, 37 suggesting cooperation between SCL and LSD1 in regulating Ter119. Even more prominent was the decrease of CD105/endoglin-expression on LSD1-kd CFU-E progenitor cells.…”
Section: Resultsmentioning
confidence: 99%
“…Like Gfi1b, TAL1/Scl is also required for embryonic hematopoiesis, but when it was deleted in adult mice, these mice were mildly anemic. While the bone marrow was defective in CFU-S assays, these mice had increased numbers of MEPs and normal percentages of CMPs and GMPs (10,21,22,42), whereas the Mtg16-null mice have fewer MEPs and an abnormal CD34 hi / Fc␥R low myeloid progenitor cell population ( Fig. 5 and 6).…”
Section: Discussionmentioning
confidence: 99%